KONTRIBUSI RUANGKU COWORKING SPACE DALAM MENGEMBANGKAN SEKTOR EKONOMI KREATIF BAGI PARA PEMUDA DI KOTA SAMARINDA - Charles Raymond Jeffrey; Heryono Susilo Utomo; Bambang Irawan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This research aims to know how Ruangku Coworking Space contribution to develop creative economic sector for youngster in Samarinda City. In this research is focused to program and activity of Ruangku Coworking Space contribution which planned and implemented by Ruangku based on theory coworking space core value from DeGuzman & Tang (2011) such as collaboration, community, sustainability, openness, and accessibility. In the other hand, this research also search about obstacle factor that faced by Ruangku Coworking Space in contribution of economic creative sector for youngster in Samarinda City. The result of the research that researcher did for Ruangku Coworking Space contribution to develop creative economic sector for youngster in Samarinda City is going well. Ruangku coworking space continuously make an event in creative economic sector. This thing is proven from successfully event implementation such as seminary, workshop, discussion by Ruangku Coworking Space in the scale of 9 from 16 creative economic subsector till now. On the other thing, Ruangku Coworking Space also undergoing the core values of the coworking space such as collaboration, community, sustainability, openness, and accessibility.Keywords : Contribution, Creative Economic, Youngster, Coworking Space